Estudo da influência dos parâmetros de usinagem no acabamento superficial do aço inoxidável austenítico AISI 304 - Melo, Marina Lolita de Assunção (Universidade Federal Rural do Semi-Árido, 2018)
In general, stainless steels have good machinability and are characterized by their high corrosion and oxidation resistance and represent a portion of the materials that are of great engineering interest. In this work, the effects of the main machining parameters on the surface integrity of the AISI 304 austenitic stainless steel subjected to the turning process were analyzed. The machining parameters chosen for the analysis were the cutting speed, feed rate and depth of cut. The tests were carried out on a horizontal CNC lathe and the surface roughness was obtained by measurements with a rugosimeter, which showed a good dispersion of the results from the standard deviation of the samples. The best finishing results were found for the lowest feed rate, which presented a marked effect on the results, regardless of the cutting speed. The best combination of the machining conditions found to obtain the lowest roughness value was the intermediate cutting speed Vc = 220 m / min and the smallest advance f = 0.1 mm / lap with a cutting depth of ap = 0.1 mm.
Monografia
Keywords: Parâmetros de usinagem; Aços inoxidáveis; Acabamento superficial; Machining parameters; Stainless steels; Surface finishing; ENGENHARIAS::ENGENHARIA MECANICA